Rent-Seeking through collective bargaining: Teachers unions and education production☆. (December 2021) - Cook, Jason; Lavertu, Stéphane; Miller, Corbin
Abstract: We explore how teachers unions affect education production by comparing outcomes between districts allocating new tax revenue amidst collective bargaining negotiations and districts allocating tax revenue well before. Districts facing union pressure increase teacher salaries and benefits, spend down reserves, and experience no student achievement gains. Conversely, districts facing less pressure hire more teachers (instead of increasing compensation) and realize significant student achievement gains. We interpret these results as causal evidence of the negative impact of teacher rent seeking on education production, as the timing of district tax elections relative to collective bargaining appears to be as good as random.